A new sensorless hysteresis direct torque control algorithm for PMSM with minimum torque ripples - Adam, Ali Ahmed; Gulez, Kayhan (EMERALD GROUP PUBLISHING LTD, 2009)
Purpose - The purpose of this paper is to describe a new method for sensorless hysteresis direct torque control (HDTC) algorithm for permanent magnet synchronous motor to minimize torque ripple and electromagnetic interference (EMI) noises. Design/methodology/approach - The design methodology is based on space vector modulation of electrical machines with digital vector control. MATLAB simulations Supported with experimental study under C+ + are used. Findings - The Simulation and experimental results of this proposed algorithm show adequate dynamic torque performance and considerable torque ripples reduction as well as lower current ripples, lower EMI noise level as compared to traditional HDTC. Research limitations/implications - This research is limited to PMSM. however the research can be extended to include induction motor as well. In addition, the actual mathematical relation between the torque ripple and flux ripple can be studied to set the flux and torque bands width in reasonable value, and this relationship can be used to select switching time of the active selected vectors. Practical implications - The implementation of the proposed algorithm ill microcontroller embedded systems is described. It requires no PI controller in the torque control loop In addition, based on existence direct torque control equipment, it is only required to change the software switching algorithm, to provide smooth torque, given that the switching frequency of the inverter module is more than or equal to 15 kHz and the system is supplied with timers. Originality/value - The algorithm used in this work utilizes the Output of two hysteresis controllers used in the traditional HDTC to determine two adjacent switching vectors per one sample time. The algorithm also uses the magnitude of the torque error, magnitude of the flux error and stator flux position to select the switching time for the selected vectors to control the applied average voltage level in such a way that the torque ripple is minimized. The selection of the switching time of the selected active vectors utilizes novel table structure which reduces the complexity of calculation. This work is directed to designers of ac motor drive system who seek smooth torque performance as well as low EMI noise level.
Keywords: Torque; Control technology; Electromagnetic fields; Microcontrollers; Computer Science; Engineering; Mathematics